2014
DOI: 10.1242/jcs.141754
|View full text |Cite
|
Sign up to set email alerts
|

p75 neurotrophin receptor evades the endolysosomal route, favouring multivesicular bodies specialised for exosomal release in neuronal cells

Abstract: The p75 neurotrophin receptor (p75, also known as NGFR) is a multifaceted signalling receptor that regulates neuronal physiology, including neurite outgrowth, and survival and death decisions. A key cellular aspect regulating neurotrophin signalling is the intracellular trafficking of their receptors; however, the post-endocytic trafficking of p75 is poorly defined. We used sympathetic neurons and rat PC12 cells to study the mechanism of internalisation and postendocytic trafficking of p75. We found that p75 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
80
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 74 publications
7
80
1
Order By: Relevance
“…A report that MAIF-dependent activation of RhoA by p75 NTR ⅐NgR complexes requires ␥-secretase-mediated release of the ICD of p75 NTR (22) and a report that this processing event follows endocytosis of p75 NTR (23) suggest the possibility that LINGO-1 may influence endosomal processing of p75 NTR . It has been reported that internalized p75 NTR accumulates most abundantly in Rab11-positive recycling endosomes (24). Thus, our observation that LINGO-1 is localized most abundantly in Rab11-positive endosomes supports the hypothesis that p75 NTR and LINGO-1 interact functionally in this endocytic compartment.…”
Section: Discussionsupporting
confidence: 88%
“…A report that MAIF-dependent activation of RhoA by p75 NTR ⅐NgR complexes requires ␥-secretase-mediated release of the ICD of p75 NTR (22) and a report that this processing event follows endocytosis of p75 NTR (23) suggest the possibility that LINGO-1 may influence endosomal processing of p75 NTR . It has been reported that internalized p75 NTR accumulates most abundantly in Rab11-positive recycling endosomes (24). Thus, our observation that LINGO-1 is localized most abundantly in Rab11-positive endosomes supports the hypothesis that p75 NTR and LINGO-1 interact functionally in this endocytic compartment.…”
Section: Discussionsupporting
confidence: 88%
“…p75 internalization is faster in hippocampal than in sympathetic neurons [53]. Endocytosis of p75 has been reported to occur via both clathrin-dependent and -independent mechanisms in sympathetic neurons [54,55] and motor neurons [56], although the functional significance of using these two routes is not known. After ligand-induced internalization in PC12 cells and sympathetic neurons, it was reported that p75 avoided the lysosome and was trafficked to Rab11 + recycling endosomes or multivesicular bodies (MVBs), where some of the receptor was exocytosed [55].…”
Section: Nt Receptor Internalizationmentioning
confidence: 99%
“…Endocytosis of p75 has been reported to occur via both clathrin-dependent and -independent mechanisms in sympathetic neurons [54,55] and motor neurons [56], although the functional significance of using these two routes is not known. After ligand-induced internalization in PC12 cells and sympathetic neurons, it was reported that p75 avoided the lysosome and was trafficked to Rab11 + recycling endosomes or multivesicular bodies (MVBs), where some of the receptor was exocytosed [55]. It is interesting that, in the chick ION, retrograde p75-mediated cell death correlated with accumulation of NGF in the neuronal soma in MVBs [57], suggesting that retrograde transport of p75 occurs in MVBs.…”
Section: Nt Receptor Internalizationmentioning
confidence: 99%
“…In sympathetic neurons and rat PC12 cells, the p75 neurotrophin receptor, also known as NGFR, escapes degradation in lysosomes after cell depolarization induced by KCl and is instead released in exosomes (Escudero et al, 2014). It was observed that after the stimulus the degradation of p75 was impaired and the receptor accumulated in MVBs (Escudero et al, 2014).…”
Section: The Diversity Of Mvbsmentioning
confidence: 99%
“…It was observed that after the stimulus the degradation of p75 was impaired and the receptor accumulated in MVBs (Escudero et al, 2014). Because p75 degradation is blocked it is likely that the MVBs, in which p75 accumulates, are not destined to deliver cargo to lysosomes, and instead it delivers to the plasma membrane.…”
Section: The Diversity Of Mvbsmentioning
confidence: 99%